Safety and feasibility of selective tongue fat reduction with injected ice‐slurry - Michael Ian Orestes; Sara Moradi Tuchayi; Ying Wang; William Farinelli; Knarik Arkun; R. Rox Anderson; Richard Thomas; Lilit Garibyan (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objectives There is growing evidence that excess adipose tissue within the head and neck contributes to obstructive sleep apnea (OSA), particularly in obese patients. This subset of the population is often difficult to treat with surgical therapies. We theorized that a novel, transcervical method of injectable cryoablation using ice‐slurry can achieve low temperatures without causing neurovascular damage or airway distress in a swine model. Methods Four Yorkshire pigs were injected with ice‐slurry comprised of normal saline and 10% glycerol cooled to −6°C via a transcervical, ultrasound guided approach. Direct laryngoscopy was used to confirm accurate placement of the slurry. Thermocouple placement at the needle‐tip was used to measure temperatures at injection site. Swine were monitored for clinical signs of tongue necrosis and airway edema for 2 months, and then euthanized. Twelve biopsy samples from the base of the tongue were collected for histology. These were assessed for presence of tissue damage, inflammation and collagen formation by a blinded board‐certified pathologist. Results Tongue tissue temperature below 10°C was achieved for 13.5 ± 1.1 min. Minimum tissue temperature was −4 ± 0.6°C. There was no clinical or pathological evidence of tongue damage to include damage to the lingual nerve or artery. There was some histologic evidence of new collagen formation in areas of the tongue. Conclusions Transcervical ultrasound‐guided ice‐slurry injection is feasible, well‐tolerated at temperatures previously shown to be capable of selectively targeting adipose tissue in the base of the tongue in a preclinical swine model, without causing neurovascular damage or airway distress when properly injected.